Pengembangan Marketing Budidaya Jamur Dengan Cara Branding Melalui Tiktok di Desa Prajegan Ponorogo - Firdaus, Muhammad Irkham; Adityo P, Satrio Pamungkas; Slamat, Muhammad Arsyad; Ramadhan, Ahmad Fathullah; Aziz, Faiz Mustafa; Wahyu, Khuza Tri; Naufal, Muhammad Hilmi; Farroby, Muhammad Husayn; Naini, In’amul Fadholis; habrianto, Aulia Dian S (An Naf'ah: Jurnal Pengabdian Masyarakat, 2024)
The impact of the Covid-19 pandemic has had a major impact on the economic sector in Indonesia. Several MSMEs experienced a decline in profits and the business ceased. This is also the case with mushroom cultivation in Prajegan village, Ponorgo. The aim of this service is to provide training on how to brand products via social media, especially TikTok, to mushroom cultivators in Prajegan Village and register IPR for these products. The method used is by creating a TikTok business account and registering IPR to protect goods from plagiarism. The results of this service resulted in MSMEs cultivating Pak Deki mushrooms as a product with digital branding via TikTok which has been registered with IPR in Prajegan village, Ponorogo.